Associações anestésicas baseadas em fármacos dissociativos reduzem a pressão intraocular (PIO) em coelhos - Mattos-Junior, Ewaldo de; Cunha, Olicies da; Moraes Barros, Luis Felipe; Hamad Minervino, Antonio Humberto; Nishimura, Lilian Toshiko; Dias, Luis Gustavo Gosuen Gonçalves [UNESP]; Gaido Cortopassi, Silvia Renata (Univ Estadual Londrina, 2014)
The aim of this study was evaluate the effects of three anesthetic combinations, ketamine-midazolam, ketamine-xylazine and tiletamine-zolazepam, on IOP in rabbits. In a experimental, blind, randomized, crossover study, six rabbits were anesthetized with each of 3 treatments in random order. Groups KM (ketamine, 30 mg/kg + midazolam, 1 mg/kg); KX (ketamine, 30 mg/kg + xylazine, 3 mg/kg); and TZ (tiletamine + zolazepam, 20 mg/kg). The drugs were mixed in the same syringe injected intramuscularly (IM) into the quadriceps muscle. IOP was measured before drug administration (baseline) and at 5-minute intervals for 30 minutes. The data were analyzed by a 2-way repeated measures ANOVA followed by Bonferroni test. All groups had significant decreases in IOP compared to baseline (p < 0.001). There was no difference between groups at any of the time points assessed (p > 0.05). Administration of either ketamine-midazolam, ketamine-xylazine, or tiletamine-zolazepam similarly decrease IOP in rabbits within 30 minutes of injection.
Dissociative anesthetic combination reduces intraocular pressure (IOP) in rabbits
Keywords: Ketamine; midazolam; Oryctolagus cuniculus; tiletamine; xylazine; zolazepam